A Microdebriefing Crisis Resource Management Program for Simulated Pediatric Resuscitation in a Community Hospital: A Feasibility Study. Issue 3 (June 2021) - Jafri, Farrukh N.; Mirante, Doreen; Ellsworth, Kelly; Shulman, Jodi; Dadario, Nicholas B.; Williams, Kimiko; Yu, Seongah; Thomas, Jinu; Kumar, Anshul; Edwards, Roger A.; Torres, Rafael E.; Straff, Dean J.
Abstract : Introduction: Crisis Resource Management (CRM) is a team training tool used in healthcare to enhance team performance and improve patient safety. Our program intends to determine the feasibility of high-fidelity simulation for teaching CRM to an interprofessional team in a community hospital and whether a microdebriefing intervention can improve performance during simulated pediatric resuscitation. Methods: We conducted a single-center prospective interventional study with 24 teams drawn from 4 departments. The program was divided into an initial assessment simulation case (pre), a 40-minute microdebriefing intervention, and a final assessment simulation case (post). Post and pre results were analyzed for each team using t tests and Wilcoxon signed-rank tests. Primary outcome measures included ( a ) completion of program, ( b ) percent enrollment, ( c ) participant reaction, and ( d ) support of continued programs on completion. Secondary outcomes included ( a ) change in teamwork performance, measured by the Clinical Teamwork Scale; ( b ) change in time to initiation of chest compressions and defibrillation; and ( c ) pediatric advanced life support adherence, measured by the Clinical Performance Tool. Results: We successfully completed a large-scale training program with high enrollment. Twenty-four teams with 162 participants improved in Clinical Teamwork Scale scores (42.8%–57.5%, P < 0.001), Clinical Performance Tool scores (61.7%–72.1%, P < 0.001), and time to cardiopulmonary resuscitation initiation (70.6–34.3 seconds, P < 0.001). Conclusions: Our center ran a well-attended, well-received interprofessional program in a community hospital site demonstrating that teaching CRM skills can improve simulated team performance in a diverse experienced cohort. Abstract : Supplemental digital content is available in the text.